Studi Komparatif Kinerja Keuangan Bank Syariah dan Konvensional di Provinsi Jambi - Sarnita Sarnita; Mustika Mustika; Tamtomo, Hario (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to compare the financial performance of Islamic banks and conventional banks operating in Jambi Province during the 2021–2023 period. The approach used is comparative quantitative, with descriptive analysis and independent sample t-tests. Five key financial ratios were analyzed in this study: Return on Assets (ROA), Return on Equity (ROE), Operating Expenses to Operating Income (BOPO), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR). Data were obtained from the quarterly financial reports of each sample bank, thus reflecting actual financial performance on a periodic and ongoing basis. The analysis shows significant differences in three key financial ratios: ROA, ROE, and BOPO. Conventional banks demonstrate higher levels of profitability and operational efficiency than Islamic banks. High ROA and ROE values reflect the effectiveness of conventional banks in generating profits from their assets and capital. Furthermore, lower BOPO ratios in conventional banks indicate a better ability to control operating costs. In contrast, no significant differences were found in the NIM and LDR ratios, indicating equality between the two types of banks in generating interest margins and disbursing credit or financing to customers. This finding has important implications for the development of the Islamic banking sector to be more competitive, particularly in terms of efficiency and profitability. Islamic banks are expected to improve their asset and operational management strategies to increase competitiveness amidst the dual banking system in Indonesia. This research also contributes to regulators in formulating policies that support the growth of Islamic banks in the regions. For academics and practitioners, this study broadens understanding of the dynamics of local banking financial performance and serves as a reference for further research on the effectiveness of the dual banking system in the regional context.